1980
DOI: 10.1073/pnas.77.10.5928
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficacies of human type I and type II interferons as antiviral and antiproliferative agents.

Abstract: Treatment of human fibroblast FS4 cultures with human type II interferon preparations induced the synthesis of at least four proteins that were similar in size to four of the five proteins induced by type I interferons (Mr 120,000, 88,000, 67,000, and 56,000). However, the M, 67,000 and 56,000 proteins were induced more strongly by type II than by type I interferon, and a counterpart of a Mr 80,000 protein induced by type I interferons was not noticeably induced by type II interferon preparations. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(82 citation statements)
references
References 36 publications
4
77
0
1
Order By: Relevance
“…2 and 3), cultured skin fibroblasts from newborn or adult donors, and some transformed or tumor cell lines (data not shown). Human fibroblast proteins with apparent molecular sizes of about 80,000 Da that are strongly induced by IFN-a but not detectably induced by IFN-y have previously been described by two other groups (7,11). It remains to be determined whether one of these proteins and the 2C12-cross-reacting protein are identical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3), cultured skin fibroblasts from newborn or adult donors, and some transformed or tumor cell lines (data not shown). Human fibroblast proteins with apparent molecular sizes of about 80,000 Da that are strongly induced by IFN-a but not detectably induced by IFN-y have previously been described by two other groups (7,11). It remains to be determined whether one of these proteins and the 2C12-cross-reacting protein are identical.…”
mentioning
confidence: 99%
“…They induce in responsive cells the synthesis of several proteins that are not detected or do exist at much lower concentrations in untreated cells. Induced proteins in mouse and human cells have been widely studied (1,5,7,10,11; for a review, see reference 6), but most of them are still poorly characterized. Also, little is known about the functional, structural, and evolutionary relationships of distinct proteins induced in cells of different species.…”
mentioning
confidence: 99%
“…CTS-51 was isolated in the process of the immune interferon production. However it does not show any antiviral activity at all, and the cytotoxic activity of CTS-51 is preserved even after the acid treatment at pH 2.0 for 24 hr, where IFN-y is known to be inactivated (Rubin and Gupta 1980). These observations seem to deny the possibilities that CTS-51 is one of the immune interferons nor that the cytotoxic activity of IFN-y preparations may be exerted by this cytotoxic substance contaminated in them.…”
Section: Discussionmentioning
confidence: 37%
“…Some of these factors, such as, for example, interferons and interleukin-2, are revealed to have a property to potentiate the cytotoxic activities of several cellular immunological systems, such as, for example, natural killer cell system or MLC derived cell mediated cytotoxicity system (Heron et al 1976(Heron et al , 1979Marx 1983). On the other hand, several other cytokines have been reported to have a property directly cytotoxic to the target cells in vitro, which include lymphotoxins (Evans 1982), tumor necrosis factors (williamson et al 1983), natural killer cytotoxic factors (Bonavida et al 1982) and immune interferons (Rubin and Gupta 1980).…”
mentioning
confidence: 99%
“…The lack of anti-adenovirus action of rlFN-~ suggests that the effect of rlFN-y depends on some mechanism(s) not shared by rlFN-a. The possibility of rlFN-y acting by a different antiviral mechanism was previously discussed by Rubin & Gupta (1980), who showed that vaccinia virus and reovirus were sensitive to IFN-y but not to IFN-a. Weil et al (1983) have shown the synthesis after rIFN-7 treatment of at least eight polypeptides not induced by rIFN-e. Antiviral states induced by IFN-cc/fl and IFN-y have been shown to be regulated with different kinetics, for both induction and extinction (Ramamurthy & Fleischmann, 1986).…”
mentioning
confidence: 99%